Virtual communities : a study on its impact as a social construct. - Tan, Kwang Hwee. (2008)
An experimental design approach to examine the impact of virtual communities as a social construct. It solicits feedback from subjects to a particular virtual community which experienced explosive growth over nine months, drawing upon their feelings and thoughts towards the virtual community.